PECULIARITIES OF TRANSLATION OF EXOTICISMS OF THE NOVEL THE PROSPECTOR BY JEAN-MARIE GUSTAVE LE CLÉZIO INTO UKRAINIAN - BOHACHENKO, Hanna (Accents and Paradoxes of Modern Philology, 2022)
The article is devoted to the analysis of the peculiarities of translation of exoticisms as a characteristic feature of the French writer Jean-Marie Gustave Le Clézio into Ukrainian. The features of the writer's style, the problem of translation of his novels are outlined. The historical context of the novel is considered as a basis for high-quality translation. The basis for the analysis is the translation of one of Le Clézio's novels "The Prospector" by Halyna Chernienko. The two major translation strategies, domestication and foreignization, are also considered in the article. The expediency of the strategy chosen by the translator is substantiated. The article offers an analysis of translation challenges faced by the translator. These ones are divided into four groups: phonetic, lexical, grammatical and stylistic challenges. In particular, it concerns proper names, lexical and grammatical features of the French language, word play and foreign inclusions (English, Creole, Latin ones). The choice of technique or method of translation is explained and analyzed on separate examples. For an in depth analysis of translation of exoticisms in the novel, the method of continuous sampling is applied. In particular, eighty units are extracted, which are divided into the following groups: geographical exoticisms (geographical objects and endemics) and ethnographic exoticisms (household and labor objects, ethnic objects and peoplerelated to labour). Geographical exoticisms account for approximately 70 percent of the exoticisms. For the translation of endemics, regular and occasional equivalence, transcoding (transliteration and transcription), calque, contextual substitution, hyponymic, hyperonymic translation and reformulation are used. The author of the article offers his own translation options for some endemics. The methods of transcoding and/or calque are used to translate toponyms. Ethnographic exoticisms account for approximately 30 percent of exoticisms. They are divided into household and labor items (units translated using the methods of transcoding, calque, contextual substitution and descriptive method), ethnic objects and people related to labor (units translated using transcoding and lexical approximation method).